Dexmedetomidine vs midazolam as preanesthetic medication in children: a meta‐analysis of randomized controlled trials. Issue 5 (6th January 2015) - Pasin, Laura; Febres, Daniela; Testa, Valentina; Frati, Elena; Borghi, Giovanni; Landoni, Giovanni; Zangrillo, Alberto; Davidson, Andrew
Summary Introduction The preoperative period is a stressing occurrence for most people undergoing surgery, in particular children. Approximately 50–75% of children undergoing surgery develop anxiety which is associated with distress on emergence from anesthesia and with later postoperative behavioral problems. Premedication, commonly performed with benzodiazepines, reduces preoperative anxiety, facilitates separation from parents, and promotes acceptance of mask induction. Dexmedetomidine is a highly selective α2‐agonist with sedative and analgesic properties. A meta‐analysis of all randomized controlled trials (RCTs) on dexmedetomidine versus midazolam was performed to evaluate its efficacy in improving perioperative sedation and analgesia, and in reducing postoperative agitation when used as a preanesthetic medication in children. Methods Studies were independently searched in PubMed, BioMedCentral, Embase, and the Cochrane Central Register of clinical trials and updated on August 15th, 2014. Primary outcomes were represented by improved sedation at separation from parents, at induction of anesthesia, and reduction in postoperative agitation. Secondary outcomes were reduction in rescue analgesic drugs, and duration of surgery and anesthesia. Inclusion criteria were random allocation to treatment and comparison between dexmedetomidine and midazolam. Exclusion criteria were adult studies, duplicate publications, intravenous administration, and no data on main outcomes. Results Data from 1033 children in 13 randomized trials were analyzed. Overall, in the dexmedetomidine group there was a higher incidence of satisfactory sedation at separation from parents (314 of 424 [74%] in the dexmedetomidine group vs 196 of 391 [50%] in the midazolam group, RR = 1.30 [1.05–1.62], P = 0.02), a reduced incidence of postoperative agitation (14 of 140 [10%] vs 56 of 141 [40%], RR = 0.31 [0.13–0.73], P = 0.008), and a significant reduction in the rescue doses of analgesic drugs (49 of 241 [20%] vs 95 of 243 [39%], RR = 0.52 [0.39–0.70], P < 0.001). There was no evidence of a higher incidence of satisfactory sedation at anesthesia induction or any reduction of duration of surgery and anesthesia. Conclusions Dexmedetomidine is effective in decreasing anxiety upon separation from parents, decreasing postoperative agitation, and providing more effective postoperative analgesia when compared with midazolam.